Effect of high pressure processing on the structural and functional properties of the protein in corn gluten meal - Sarina Ma; Shimin Gui; Ruixia Hao; Xili Dege; Meili Zhang (CyTA - Journal of Food)
The presentation of high pressure processing (HPP) on corn starch has been reported, but the effect on protein in corn gluten meal (CGM) is rarely explored. The purposes of this study were to investigate the effect of HPP treatment on structural and functional properties of the protein in CGM. Protein was treated at 200–600 MPa for 5–15 min. Results showed that HPP treatment increased protein solubility, water and oil binding capacities, emulsion stability, foaming and foam stability. Protein which treated at 400 MPa for 15 min had the more enhanced functionality. Moreover, under this condition, the protein aggregates gradually dissociated, and the particle size decreased. These results indicated that the functional groups and structure of CGM protein were affected by the HPP treatment. We hope to convert an underutilized material into a valuable one through HPP in food industry.